Neonatal jaundice and developmental impairment among infants in Kilifi, Kenya. (5th February 2020) - Magai, Dorcas N.; Mwaniki, Michael; Abubakar, Amina; Mohammed, Shebe; Gordon, Anne L.; Kalu, Raphael; Mwangi, Paul; Koot, Hans M.; Newton, Charles R.
Abstract: Background: Neonatal jaundice (NNJ) is common in sub‐Saharan Africa (SSA), and it is associated with sepsis. Despite the high incidence, little has been documented about developmental impairments associated with NNJ in SSA. In particular, it is not clear if sepsis is associated with greater impairment following NNJ. Methods: We followed up 169 participants aged 12 months (57 cases and 112 controls) within the Kilifi Health Demographic Surveillance System. The diagnosis of NNJ was based on clinical laboratory measurement of total serum bilirubin on admission, whereas the developmental outcomes were assessed using the Developmental Milestones Checklist and Kilifi Development Inventory. Results: There were significant differences between the cases and controls in all developmental domains. Cases scored lower in language functioning (mean [ M ] = 6.5, standard deviation [ SD ] = 4.3 vs. M = 8.9, SD = 4.6; p < .001); psychomotor functioning ( Mdn = 23, interquartile range [IQR] = 17–34 vs. Mdn = 31.0, IQR = 22.0–44.0; Mann–Whitney U = 4, 122, p = .002); and socio‐emotional functioning ([ Mdn = 30.0, IQR = 27.0–33.0 vs. Mdn = 34.0, IQR = 30.0–37.0], Mann–Whitney U = 4, 289, p < .001). There was no evidence of association between sepsis and psychomotor ( r pb = −.2, p = .214), language ( r pb = −.1, p = .510), and socio‐emotional functioning ( r pb = .0, p = .916). Significant and medium to large portions of the variance (34–64%) in the developmental outcomes among children who survived NNJ were associated with home birth, low maternal education, and feeding problems during the first days of life. Conclusions: NNJ is associated with developmental impairments in the early childhood years; however, NNJ associated with sepsis does not lead to more severe impairment. Prenatal and postnatal care services are needed to reduce the negative impact of NNJ for children from low resourced settings.